Preclinical Study of Biofunctional Polymer-Coated Upconversion Nanoparticles. (15th April 2019) - Guryev, Evgenii L; Shilyagina, Natalia Y; Kostyuk, Alexey B; Sencha, Ludmila M; Balalaeva, Irina V; Vodeneev, Vladimir A; Kutova, Olga M; Lyubeshkin, Alexander V; Yakubovskaya, Raisa I; Pankratov, Andrei A; Ingel, Faina I; Novik, Tamara S; et al.
Abstract: Upconversion nanoparticles (UCNPs) are new-generation photoluminescent nanomaterials gaining considerable recognition in the life sciences due to their unique optical properties that allow high-contrast imaging in cells and tissues. Upconversion nanoparticle applications in optical diagnosis, bioassays, therapeutics, photodynamic therapy, drug delivery, and light-controlled release of drugs are promising, demanding a comprehensive systematic study of their pharmacological properties. We report on production of biofunctional UCNP-based nanocomplexes suitable for optical microscopy and imaging of HER2-positive cells and tumors, as well as on the comprehensive evaluation of their pharmacokinetics, pharmacodynamics, and toxicological properties using cells and laboratory animals. The nanocomplexes represent a UCNP core/shell structure of the NaYF4:Yb, Er, Tm/NaYF4 composition coated with an amphiphilic alternating copolymer of maleic anhydride with 1-octadecene (PMAO) and conjugated to the Designed Ankyrin Repeat Protein (DARPin 9_29) with high affinity to the HER2 receptor. We demonstrated the specific binding of UCNP-PMAO-DARPin to HER2-positive cancer cells in cultures and xenograft animal models allowing the tumor visualization for at least 24 h. An exhaustive study of the general and specific toxicity of UCNP-PMAO-DARPin including the evaluation of their allergenic, immunotoxic, and reprotoxic properties was carried out. The obtained experimental body of evidence leads to a conclusion that UCNP-PMAO and UCNP-PMAO-DARPin are functional, noncytotoxic, biocompatible, and safe for imaging applications in cells, small animals, and prospective clinical applications of image-guided surgery.